Travel and tourism in Britain, 1700-1914.
1 online resource (2048 pages).
Keywords: The British led the way in holidaymaking. This four-volume primary resource collection brings together a diverse range of texts on the various forms of transport used by tourists, the destinations they visited, the role of entertainments and accommodation and how these affected the way that tourism evolved over two centuries.